LINC00908 Inactivates Wnt/β‐Catenin Signaling Pathway to Inhibit Prostate Cancer Cell Stemness via Upregulating GSK3B and FBXW2 - Han Guan; Qiang Hu; Lilin Wan; Can Wang; Yifeng Xue; Ninghan Feng; Chenggui Zhao; Ming Chen; Zonghao You (Cancer Medicine, 2025)
ABSTRACT Background Chemotherapy and androgen‐deprivation treatment are the curative approaches utilized to suppress prostate cancer (PCa) progression. However, drug resistance and metastasis are extensive and hard to overcome even though remarkable progress has been made in recent decades. The cancer stem cell‐related theoretical model explains the distinct molecular characteristics of cancer, its relapse, metastasis, and drug resistance. Meanwhile, noncoding RNA functions in the formation of drug resistance and metastasis in most cancers. The long intergenic nonprotein coding RNA 908 (LINC00908) has been reported to restrain cell proliferation, migration, and invasion of some cancers like triple‐negative breast cancer, diffuse large B‐cell lymphoma, PCa, and so on. However, its role in stemness for PCa remains unclear. Methods We delved into the impact of LINC00908 in PCa cell stemness and the principal molecular mechanism. Then, the impact of LINC00908 on PCa cell stemness and its corresponding mechanism was explored by using functional assays and bioinformatics evaluation. Results We found that LINC00908 was low‐expressed in PCa cells, and it exerted suppressive functions in PCa cell stemness and tumor growth. Additionally, we revealed that LINC00908 down‐regulation was mediated by the HDAC2‐p300‐YY1 transcription complex. Moreover, LINC00908 up‐regulated glycogen synthase kinase 3 beta (GSK3B) via sponging miR‐3179. Meanwhile, LINC00908 deployed DEAD‐box helicase 3 X‐linked (DDX3X) to facilitate the stabilization of F‐box and WD repeat domain containing 2 (FBXW2) mRNA. Importantly, LINC00908 enhanced GSK3B and FBXW2 expression to induce the ubiquitination of β‐catenin protein, leading to Wnt pathway inactivation. Conclusion These results reveal that LINC00908 inhibits PCa cell stemness via inactivating the GSK3B/FBXW2‐regulated Wnt pathway, which might enrich people's knowledge of PCa stemness and provide some new potential biomarkers for PCa.